Exploring the Relationship between Opportunity and Self-Control in Youth Exposure to and Sharing of Online Hate Content - Turner, Noah (Terrorism and political violence, 2023)
The rise of the Internet has dramatically increased the degree to which youth may be exposed to online hate content, and simplified the process of sharing this content with others. Viewing messages that contain hate speech or language vilifying others can increase an individual’s risk of radicalization to extremist views and the acceptance of violent ideologies. Researchers have begun to explore the risk factors for exposure to such content, with prior studies demonstrating a relationship between low self-control and online activities being important correlates. Few studies have utilized youth samples to assess these relationships, or explored the voluntary consumption and sharing of content. This study attempts to address this gap in the literature using self-report responses provided by a sample of 1,193 youths in South Australia. A series of quantitative models are estimated assessing the relationships between self-control, opportunities to view content using both on and off-line measures, and four dependent variables related to exposure to or sharing of hate content. The implications of this analysis for our understanding of the utility of criminological theory to radicalization and countering violent extremism are discussed in detail.